Auditory processing following infantile spasms: An event‐related potential study. (12th April 2017) - Fosi, Tangunu; Werner, Klaus; Boyd, Stewart G.; De Haan, Michelle; Scott, Rod C.; Neville, Brian G.
Summary: Objectives: To investigate acoustic auditory processing in patients with recent infantile spasms (IS). Methods: Patients (n = 22; 12 female; median age 8 months; range 5–11 months) had normal preceding development, brain magnetic resonance imaging (MRI), and neurometabolic testing (West syndrome of unknown cause, uWS). Controls were healthy babies (n = 22; 11 female; median age 6 months; range 3–12 months). Event‐related potentials (ERPs) and psychometry (Bayley Scales of Infant Development, Second Edition, BSID‐II) took place at a month following IS remission. Results: Following a repeated pure tone, uWS patients showed less suppression of the N100 at the mid‐temporal electrodes (p = 0.006), and a prolonged response latency (p = 0.019). Their novelty P300 amplitude over the mid‐temporal electrodes was halved (p = 0.001). The peak of the novelty P300 to environmental broadband sounds emerged later over the left temporal lobe in patients (p = 0.015), the lag correlating with duration of spasms (r = 0.547, p = 0.015). BSID‐II scores were lower in patients (p < 0.001), with no correlation to ERP. Significance: Complex acoustic information is processed poorly following IS. This would impair language. Treatment did not reverse this phenomenon, but may have limited its severity. The data are most consistent with altered connectivity of the cortical acoustic processing areas induced by IS.